Factors that determine donors intention to endow cash waqf for microenterprises in Malaysia - Abdul Razak, Dzuljastri; Mohamed Zakaria, Fodol; Ahmed Abdillahi, Jama; Ali Ahmad, Burhan (DergiPark Akademik, 2019)
In the modern era, the waqf concept has become more sophisticated and comprehensive and through it, many financial products and social programs have been developed, for instance, cash waqf and some security papers such as Shares-Waqf, Sukuk-Waqf, etc. Therefore, cash waqf can also be used in microenterprises to efficiently channel funds (interest free-funds) to microenterprises to alleviate poverty and decrease unemployment. Recently, several products for cash waqf in microenterprises have been established, but they could not reach their targets since they need a significant contribution from Muslims in the society. Thus, lacuna exists to assess the intention of donners towards cash waqf for microenterprises empirically. Therefore, this paper aims to determine the factors influencing the intention to endow cash waqf for microenterprises based on four variables namely, the concept of cash waqf, trust, religiosity motivation, and social culture. The survey method was carried out on 200 respondents in Kuala Lumpur, Malaysia. Factor analysis and multiple regression were used to estimate the relationship between variables. The results indicated that the concept of cash waqf, trust, and social culture have a significant relationship with the intention to endow CWME. Hence, practitioners can emphasize on the three factors in their marketing efforts to promote CWME. Academicians may also benefit by conducting more research in this area of knowledge.